Career Guidance Planning Program at SMA Muhammadiyah 1 Karanganyar - Rahmawati, Sufiyah; Utami, Kharisma Vina; Larasati, Rachmalia Dewi; Shobabiya, Mahasri (Lembaga Riset Mutiara Akbar, 2023)
Guidance and counseling is an integral part of education that consciously positions students' abilities to explore, choose, plan and make decisions to achieve their future. The importance of career development among high school (SMA) students is becoming increasingly urgent along with rapid developments in the world of education and work. Not all teenagers can make career decisions easily, and many students experience episodes of doubt before settling on a career path. These doubts are manifested as difficulties that individuals face when deciding on a career. This research uses a qualitative approach. The type of research used by researchers is a qualitative approach. This research aims to investigate the career guidance planning program at SMA Muhammadiyah 1 Karanganyar, with a focus on students' understanding of their potential, knowledge of various career options, and development of relevant skills. This research uses a qualitative approach. The data collection technique is through in-depth interviews with resource persons. This career guidance is given to all students of SMA Muhammadiyah 1 Karanganyar starting from class 10 to class 12. The career planning program in class 11 places more emphasis on repeating career guidance information in class 10 such as counseling on college pathways through SNBT or SNBP planning. In class 12, career guidance is carried out through outreach by state and private higher education institutions from D3 to S1 level. The positive impact arising from the career guidance planning program at SMA Muhammadiyah 1 Karanganyar is that it makes it easier for students to determine the steps they will take in determining their career. Students become more likely to have a more organized view of the future.